Multimedia Development Based on Android in The Prevention and Handling of Injuries to Sports Players - Akbar, Kemas Ikral; Soegiyanto, Soegiyanto; Pramono, Harry (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The purpose of this study are: to develop Android-based multimedia in prevention, to manage injuries to athletes, to knows the development results developed as a medium of knowledge and information on injuries by using the method (1) initial analysis, (2) prevention needs analysis and injury management, (3) analysis of making counts, (4) planning the initial product, (5) expert validation, (6) revisions, (7) small scale tests, (8) revisions, (9) product testing, (10) revisions. The results of the validation of material experts I and II which covered all aspects obtained a percentage value of 83% and 90%, while the validation of programmer I and II experts obtained a percentage value of 93% and 86% with very good categories. The results of small-scale trials obtained a percentage value with trainers and futsal extracurricular students as much as 84% while the results of large-scale product trials obtained a percentage value of 89% with very good categories. Conclusions and suggestions in this study produce PPC futsal multimedia products based on android applications in the prevention and handling of injuries. The suggestion that PPC futsal multimedia can be used as a science and information related to futsal sports injuries that can be used by coaches and extracurricular students.